Migratory flows in Spain: a nonparametric and semiparametric approach - Adolfo Maza; José Villaverde (European Regional Science Association (ERSA), 2004)
Labour market is characterized in Spain by a high persistence in unemployment rates. One of the main reasons of this persistence is the lack of labour mobility. The present paper addresses this issue empirically and analyses the determinants of migration in Spain from a regional standpoint. We used a panel data set that includes annual bilateral migratory flows between the 17 Spanish regions from 1995 through 2000. For this purpose, after a descriptive analysis, we develop a nonparametric approach to show the factors that influence in the magnitude of migratory flows. Later on, semiparametric estimation techniques are applied to provide more econometric evidence regarding migratory flows. Main conclusions are as follows: first, a high inertia in the migratory flows exists, that it is to say, migratory movements are very persistent; second, migratory flows mainly respond, though weakly, to the differentials of wages, unemployment rates and house prices between regions; third, migratory flows are also affected, to a great extent, by non economic factors. Keywords: migratory flows, regions, unemployment, wages. JEL classification: J61, R23, C14
Keywords: J61; R23; C14; 330; migratory flows; regions; unemployment; wages